Formal aspects of component software : 12th International Conference, FACS 2015, Niterói, Brazil, October 14-16, 2015, Revised selected papers /: 12th International Conference, FACS 2015, Niterói, Brazil, October 14-16, 2015, Revised selected papers. (2016) - Unknown
No abstract available